2018
DOI: 10.4315/0362-028x.jfp-17-405
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Toxigenic Fungi and Mycotoxins on Root Herbs from Chinese Markets

Abstract: Herbs derived from roots, leaves, flowers, or fruits of plants are unavoidably contaminated with fungi and mycotoxins during growth, harvest, and storage, thereby posing a health threat to humans. Especially, root herbs (RHs) are more easily contaminated with fungi and mycotoxins because the roots are in direct contact with the soil. Here, we investigated the occurrence of fungi, aflatoxins (AFs), and ochratoxin A (OTA) in eight RHs that are used as medicines, beverages, dietary supplements, and functional foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Zheng et al [34] also showed the widespread fungal contamination in 15 medicinal herbs collected from China. Meanwhile, Su et al [35] found that 48 samples of eight root herbs from Chinese markets are all contaminated by fungi. In all these studies, Aspergillus and Penicillium are identified as the most common contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al [34] also showed the widespread fungal contamination in 15 medicinal herbs collected from China. Meanwhile, Su et al [35] found that 48 samples of eight root herbs from Chinese markets are all contaminated by fungi. In all these studies, Aspergillus and Penicillium are identified as the most common contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…Fungi of the types: Aspergillus , Penicillium , Fusarium and Alternaria , under favorable conditions, are capable of producing secondary metabolites—mycotoxins [ 7 , 42 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Mycotoxinsmentioning
confidence: 99%
“…Therefore, the plant has been studied for mycotoxicological contamination. The results showed that sampled ginseng roots had significant levels of AFs which exceeded acceptable standards [38,65] (Table 5).…”
Section: Panax Ginseng (Ginseng)mentioning
confidence: 97%
“…Other countries have set similar regulations, although the maximum tolerated levels can vary. For example, the maximum limit for aflatoxin in India appears to be much higher (30 µg/kg) than in other countries [37,38]. In China, 5 to 20 µg/kg is the maximum limit depending upon the classification of the medicinal herb under consideration [33,36,39].…”
Section: Regulations Concerning Production and Distribution Of Medicimentioning
confidence: 99%